Preparation of ionic liquids and their application. - Wasserscheid, Peter; Paape, Natalia; Bösmann, Andreas; Schulz, Peter (2009)
The present invention relates to chem. compds. comprising of formula [X(CHRa)n-CH(Ra)SO3]- [X = F, Cl, Br, acyl; n = 1 - 3; Ra = H, C1-12 alkyl; Rb = C1-12], their prepn. and application. The chem. compds. are preferably ionic liqs. Compd. I was prepd. by addn. of the anion of 1-butyl-3-methylimidazolium chloride to 1,4-butane sulfone. [on SciFinder(R)]
Keywords: imidazolium chloride sultone anion addn; sulfonate imidazolium prepn ionic liq; tetraalkylammonium sulfonate prepn ionic liq